Jacobite Past, Loyalist Present - (:unkn) unknown (My University, 2003)
This article is the first analysis of Gaelic sources relating to the involvement of Scottish Highlanders in warfare in North America from the opening of the French and Indian War to the end of the American Revolution. A careful reading of these primary sources — almost totally unknown to historians — can provide a unique window on the sentiments and reasoning of Highlanders regarding these conflicts. This analysis of contemporary Gaelic poetry demonstrates that there is a high degree of continuity and consistency in the ideological framework of the lines of political argumentation from the Jacobite era through the end of the American Revolution.
Keywords: Scottish Highlanders; Scottish Soldiers; Highland Loyalists; American Revolution; Scottish Gaelic Poetry; Jacobitism